2014
DOI: 10.1111/j.1755-3768.2014.3423.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual acuity loss in open‐angle glaucoma patients: causes and risk factor

Abstract: Purpose To identify causes of visual acuity loss in open angle‐glaucoma (OAG) patients and to determine associated risk factors. Methods From the visual field database of the University Medical Center Groningen, 400 patients with at least 3 reliable visual fields were randomly selected. Of these, 233 had OAG. OAG patients with a visual acuity of 0.5 or less in at least one eye were considered as cases; controls had to have a visual acuity above 0.5 in both eyes. Causes of visual acuity loss were determined fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…In a study by N Ayachoua, 17% of cases of decreased vision were due to cataract. 3 In another report it was 50.4%. 14 Cataract is a common cause of decreased visual equity in the elderly and it is a common reversible cause of decreased visual acuity in glaucoma patients.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…In a study by N Ayachoua, 17% of cases of decreased vision were due to cataract. 3 In another report it was 50.4%. 14 Cataract is a common cause of decreased visual equity in the elderly and it is a common reversible cause of decreased visual acuity in glaucoma patients.…”
Section: Discussionmentioning
confidence: 85%
“…11 A study by N Ayachoua had reported visual loss with glaucomatous optic atrophy in 40% of patients. 3 In Africa, up to 70% of glaucoma patients presented with advanced glaucomatous optic atrophy in better eye. 12 The frequency of glaucomatous optic atrophy was higher in our patients in comparison to other studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations